Curvature structure triboelectric nanogenerator for harvesting human motion energy and cheerleading training monitoring - Jing Wang; Anchao Feng (AIP Advances)
Recently, self-powered wearable sports monitoring devices have garnered widespread attention. However, earlier sensor devices suffer from limitations such as single-mode operation, unstable output, and high power consumption. In this study, we leveraged the curvature effect to enhance the performance of triboelectric nanogenerators (C-TENGs) for harvesting micro-mechanical energy. The C-TENG demonstrated an open-circuit voltage (Voc) of 507.07 V, a short-circuit current (Isc) of 80.03 μA, and a transfer charge (Qsc) of 100.47 nC. Additionally, the C-TENG achieved a high output power of 3.22 mW with a 4 MΩ external resistor. Furthermore, a C-TENG sensor array embedded in shoes can monitor the cheerleading performer’s gait by analyzing the differences in signals from three C-TENG sensors. This includes detecting slow walking, brisk walking, and jumping. This innovative sensing design differs from previous single-signal outputs and effectively avoids sensing errors caused by sensor fatigue and loss.